The Relationship Between Corporate Social Responsibility And Earnings Management In Industrial Companies Listed In Arab Financial Markets - علي, عفراء; نصّار, باسل; محمد, ولاء (Latakia University Journal - Economic and Legal Sciences Series, 2021)
this research aims to study the relationship between corporate social responsibility and earning management during the period from (2016) to (2019), using a sample consisting of (64) industrial companies listed in the Arab financial markets. The study used three dimensions to measure corporate social responsibility (corporate governance, the environment, and employees) and the content analysis of the financial statements has been used to measure these dimensions. The modified Jones model was adopted to measure earning management as it is the most used measure in previous studies to measure earning management. This model is based on measuring voluntary benefits. The results showed statistically significant and positive effect between each of the dimensions of corporate social responsibility (governance, employees, and environment) and earning management.